An Analysis of Grammatical Errors in Writing Made by Sixth Semester Students at English Education Program of Batanghari University Academic Year 2016/2017 - Ryan Raditya; Wennyta Wennyta; Nurul Fitri (JELT: Journal of English Language Teaching, 2017)
AbstractThis research is purposed to analyze the grammatical errors in writing made by sixth semester students at English education program of Batanghari University academic year 2016/2017. The method of this research is descriptive qualitative. The sample of this research is sixth semester students at English education program of Batanghari University and choosing them by using random sampling technique. The instrument of the research is test, the test is conducted two times at A and B class. Based on the result, sixth semester students often make grammatical errors in their writing, the errors are analyzed based on four categories, there are Fragment, Run-Ons, Problems with Subject-Verb Agreement, and Verb Problems. Then the researcher calculates the total errors made by sixth semester students by using the formula in order to find out the most common grammatical error. It is found that the most grammatical error made by students is Fragment which is 32,95% , and the smallest percentage of errors made by students is Verb problems which is 19,31%. Based on the finding above, the researcher can conclude that sixth semester students need to study about grammar deeper in order to avoid misunderstanding in their writing.Keywords: Grammatical errors, Writing